2014
DOI: 10.1371/journal.pone.0090883
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Modulate Albumin-Induced Renal Tubular Inflammation and Fibrosis

Abstract: Bone marrow-derived mesenchymal stem cells (BM-MSCs) have recently shown promise as a therapeutic tool in various types of chronic kidney disease (CKD) models. However, the mechanism of action is incompletely understood. As renal prognosis in CKD is largely determined by the degree of renal tubular injury that correlates with residual proteinuria, we hypothesized that BM-MSCs may exert modulatory effects on renal tubular inflammation and epithelial-to-mesenchymal transition (EMT) under a protein-overloaded mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 42 publications
2
61
0
Order By: Relevance
“…In addition to suppressing the secretion of TNF- α by activated macrophages, this protein induces a change in the TGF- β 1/TGF- β 3 balance, from a profibrotic high ratio to an antifibrotic low ratio [77]. These results are confirmed in a coculture model in which recombinant TSG-6 partially reproduced the effects of MSCs [62]. …”
Section: Antifibrotic Effects Of Mesenchymal Stromal Cells Therapymentioning
confidence: 98%
“…In addition to suppressing the secretion of TNF- α by activated macrophages, this protein induces a change in the TGF- β 1/TGF- β 3 balance, from a profibrotic high ratio to an antifibrotic low ratio [77]. These results are confirmed in a coculture model in which recombinant TSG-6 partially reproduced the effects of MSCs [62]. …”
Section: Antifibrotic Effects Of Mesenchymal Stromal Cells Therapymentioning
confidence: 98%
“…32 The antiinflammatory and antifibrotic activities of BM-MSCs were indicated by attenuation of the TNF-a and NF-jB overexpression in a recent model of albumininduced renal tubular inflammation and fibrosis. 37 The MSCs have a prominent immunomodulatory property that leads to the downregulation of inflammatory reactions. 38 Moreover, BM-MSCs also significantly suppressed the renal p38-MAPK, caspase-3 and Bax expressions in CDDP-treated rats.…”
Section: 17mentioning
confidence: 99%
“…Hence, engrafted MSCs might modify the injured kidney by secreting these factors to trigger intracellular signaling in target cells or neighboring cells. We demonstrated that bone marrow MSCs modulate albumin-induced renal tubular inflammation and fibrosis by secreting hepatocyte growth factor and TNF-stimulated gene 6 (TSG-6) both in vitro and in vivo [70] . Conditioned medium of human umbilical cord blood-derived MSCs significantly inhibited α-SMA, TGF-β 1 , collagen I, and Hsp 47 upregulation and E-cadherin and BMP-7 downregulation induced by TGF-β 1 in NRK-52E cells in a dose-dependent manner through secretion of humoral factors [71] .…”
Section: Paracrine and Immunomodulationmentioning
confidence: 99%